The effect of losing and winning on cheating and effort in repeated competitions - Necker, Sarah; Paetzel, Fabian (Journal of Economic Psychology, 2023)
Competitive rewards are often assigned on a regular basis, e.g., in annual salary negotiations or employee-of-the-month schemes. The repetition of competitions can imply that opponents are matched based on earlier outcomes. Using a real-effort experiment, we examine how cheating and effort evolve in two rounds of competitions in which subjects compete with different types of opponents in the second round (random/based on the first-round outcome). We find that (i) losing causes competitors to increase cheating in the second round while winning implies a tendency to reduce cheating. A similar effect is found with regard to effort, as losers increase effort to a larger extent than winners. (ii) Competitor matching does not significantly affect behavior.
CRIS-Team Scopus Importer:2023-08-18
Keywords: 2260; 2910; 3040; Cheating; Competition; Competitor; Effort; Laboratory experiment; Social recognition; Diskriminierung